2011
DOI: 10.1075/dapsac.46.03tsa
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 1. Humour in politics and the politics of humour

Abstract: In this chapter, the authors offer a working definition of political humour and summarise its main aspects as discussed in the relevant literature: the genres where political humour surfaces or dominates; the reasons why political criticism is so often encoded in humorous terms; and the (side-)effects of political humour. They also discuss the so-called “inherent ambiguity of humour”, thus explaining why political humour does not necessarily influence politics. Rather than provoking social and political change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 0 publications
0
22
0
7
Order By: Relevance
“…In this sense, it is once again confirmed that political jokes are a momentary social disruption (through symbolically attacking persons in power) which has no lasting or radical effects but eventually reinforces the existing sociopolitical order, rather than an act of rebellion against the financial markets and agencies (cf. Billig 2005: 200-235;Davies 2011;Tsakona & Popa 2011;Tsakona 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, it is once again confirmed that political jokes are a momentary social disruption (through symbolically attacking persons in power) which has no lasting or radical effects but eventually reinforces the existing sociopolitical order, rather than an act of rebellion against the financial markets and agencies (cf. Billig 2005: 200-235;Davies 2011;Tsakona & Popa 2011;Tsakona 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although ever since then research on political humour has expanded to a significant extent (see among others Tsakona & Popa 2011, 2013Tsakona 2015 and references therein), political jokes do not seem to be the most popular genre of political humour among humour scholars. Other genres such as political cartoons, satirical shows (whether on TV or in the form of stand-up comedy), politicians' humour, and, more recently, Raskin (1985: 222-246) discusses jokes from both Communist and non-communist countries and further specifies their topics.…”
Section: Introductionmentioning
confidence: 99%
“…I use and define humour like Villy Tsakona and Diana Elena Popa (2011), as an umbrella term for phenomena related to humour: mockery, parody, ridicule satire, irony, etc. Humour is also a social deed.…”
Section: H U M O U Rmentioning
confidence: 99%
“…Political humour includes any humorous text that not only makes reference to politics, but achieves the goal of politics by dealing with political issues, people, processes, events, or institutions. It is known to be a communicative resource for spotting, highlighting, and attacking incongruities originating in political discourse and action (Tsakona & Popa, 2011, Chun, 2004, & Warner, 2007. These incongruities are those political shortcomings that constitute a deviation from political norms, and consequently, in view of this nonconformity, become undoubtedly source material for the media.…”
Section: Political Cartoons and Political Humourmentioning
confidence: 99%